Novel Food Fermentation Technologies - Ojha, K. Shikha; Tiwari, Brijesh K.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
Novel Food Fermentation Technologies provides a comprehensive overview of innovations in food fermentation technologies and their application. Current novel technologies for microbial culture production and preservation are covered in detail, as are fermentation techniques for the production of bioactives from various food matrices, including food processing by-products and waste. Readers are provided with a close look at thermal and non-thermal technologies applicable to fermented food products. The text covers immobilization, microencapsulation technologies and novel preservation techniques for cultures in fermentation. In-depth studies of high pressure processing, pulsed electric field, power ultrasound and gamma irradiation in fermentation are provided in addition to novel thermal and non-thermal technologies and process analytical techniques. A wide variety of fermented products are covered, including meat, marine-based, grain-based, dairy and vegetable-based products. Current technologies for extraction of bioactives are examined, as are current innovations in fermented food packaging. Readers are presented with current and future challenges in food fermentation as well. As a comprehensive reference for food fermentation, this work provides up-to-date insights into emerging fermentation technologies which facilitate the processing of wholesome and safe food products.
Novel Food Fermentation Technologies -- Novel preservation techniques for microbial cultures -- Novel Microbial Immobilization Techniques -- High pressure processing for food fermentation -- Pulsed electric field and fermentation -- Ultrasound and food fermentation -- Gamma irradiation and fermentation -- Novel thermal technologies and fermentation -- Novel Fermented Dairy Products -- Novel fermented meat products -- Novel fermented marine based products -- Novel fermented grain based products -- Novel fermented fruit and vegetable based products -- Bioactive compounds from fermented food products -- Innovations in packaging of fermented food products.
Keywords: Food science; Chemistry, Organic; Industrial microbiology; Food Science; Organic Chemistry; Industrial Microbiology